Sense of agency is related to gamma band coupling in an inferior parietal-preSMA circuitry - Ritterband-Rosenbaum, Anina; Nielsen, Jens B.; Christensen, Mark S. (Frontiers in Human Neuroscience, 2014)
In the present study we tested whether sense of agency (SoA) is reflected by changes in coupling between right medio-frontal/supplementary motor area (SMA) and inferior parietal cortex (IPC). Twelve healthy adult volunteers participated in the study. They performed a variation of a line-drawing task (Nielsen, 1963;Fourneret and Jeannerod, 1998), in which they moved a cursor on a digital tablet with their right hand without seeing the hand. Visual feedback displayed on a computer monitor was either in correspondence with or deviated from the actual movement. This made participants uncertain as to the agent of the movement and they reported SoA in approximately 50% of trials when the movement was computer-generated. We tested whether IPC-preSMA coupling was associated with SoA, using dynamic causal modelling (DCM) for induced responses (Chen et al., 2008;Herz et al., 2012). Nine different DCMs were constructed for the early and late phases of the task, respectively. All models included two regions: a superior medial gyrus (preSMA) region and a right supramarginal gyrus (IPC) region. Bayesian models selection (Stephan et al., 2009) favoured a model with input to IPC and modulation of the forward connection to SMA in the late task phase, and a model with input to preSMA and modulation of the backward connection was favoured for the early task phase. The analysis shows that IPC source activity in the 50-60Hz range modulated preSMA source activity in the 40-70 Hz range in the presence of SoA compared with no SoA in the late task phase, but the test of the early task phase did not reveal any differences between presence and absence of SoA. We show that SoA is associated with a directionally specific between frequencies coupling from IPC to preSMA in the higher gamma (ɣ) band in the late task phase. This suggests that SoA is a retrospective perception, which is highly dependent on interpretation of the outcome of the performed action.